Gravitational lensing of active galactic nuclei. - Hewitt, J N (1995)
Most of the known cases of strong gravitational lensing involve multiple imaging of an active galactic nucleus. The properties of lensed active galactic nuclei make them promising systems for astrophysical applications of gravitational lensing; in particular, they show structure on scales of milliseconds of arc to tens of seconds of arc, they are variable, and they are polarized. More than 20 cases of strong gravitational lenses are now known, and about half of them are radio sources. High-resolution radio imaging is making possible the development of well-constrained lens models. Variability studies at radio and optical wavelengths are beginning to yield results of astrophysical interest, such as an independent measure of the distance scale and limits on source sizes.